Design for social innovation on the diffusion of the vegan lifestyle - Weiss, Marco Antônio (2019)
This paper aims to describe, systemically, a proposal that can enable access to vegan products and spread this lifestyle. Methodological procedures include a bibliographical research and a field data collection with the application of a questionnaire. Finally, a systemic map was designed. As a result, the concept of collaborative organizations – described by Manzini (2008) – is proposed in vegan food production ventures, promoting their notoriety and the food awareness of the vegan lifestyle.